Association of hospital volume and long-term survival after esophagectomy: A systematic review and meta-analysis - Wang, Qing; Mine, Shinji; Nasu, Motomi; Fukunaga, Tetsu; Nojiri, Shuko; Zhang, Chun-Dong (Frontiers in Surgery, 2023)
Background: It remains controversial whether esophageal cancer patients may benefit from esophagectomy in specialized high-volume hospitals. Here, the effect of hospital volume on overall survival (OS) of esophageal cancer patients post esophagectomy was assessed. Methods: PubMed, Embase, and Cochrane Library were systematically searched for relevant published articles between January 1990 and May 2022. The primary outcome was OS after esophagectomy in high- versus low-volume hospitals. Random effect models were applied for all meta-analyses. Subgroup analysis were performed based on volume grouping, sample size, study country, year of publication, follow-up or study quality. Sensitivity analyses were conducted using the leave-one-out method. The Newcastle-Ottawa Scale was used to assess the study quality. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidance, and was registered (identifier: INPLASY202270023). Results: A total of twenty-four studies with 113,014 patients were finally included in the meta-analysis. A significant improvement in OS after esophagectomy was observed in high-volume hospitals as compared to that in their low-volume counterparts (HR: 0.77; 95% CI: 0.71–0.84, P<0.01). Next, we conducted subgroup analysis based on volume grouping category, consistent results were found that high-volume hospitals significantly improved OS after esophagectomy than their low-volume counterparts. Subgroup analysis and sensitivity analyses further confirmed that all the results were robust. Conclusions: Esophageal cancer should be centralized in high-volume hospitals.